The Effect of Lens Focal Length on the Output Characteristics of 1.55 μm Tunable External-Cavity Semiconductor Lasers - Xuan Li; Linyu Zhang; Wei Luo; Junce Shi; Zhaoxuan Zheng; Huiyin Kong; Meiye Qiu; Kangxun Sun; Zaijin Li; Yi Qu; Zhongliang Qiao; Lin Li (Photonics)
The 1.55 μm TECSL has excellent characteristics such as wide tuning, narrow linewidth, high SMSR, and high output power and has a wide range of applications in optical communications, spectral sensing, gas detection, atomic physics, and biomedicine. For the TECSL, the choice of collimating lens is very significant. In order to obtain a wider tuning range, five structures are constructed in this paper to investigate the effect of lens focal length on the output characteristics of 1.55 μm TECSL. It is shown that when the lens focal length is 4.51 mm, the minimum threshold current is 52 mA, the maximum output power is 42.36 mW, the maximum SMSR is 62.15 dB, the narrowest linewidth is 0.26 nm, and 152.3 nm (1458.2~1610.5 nm) can be tuned continuously. It is shown that different lens focal lengths affect the output characteristics of the TECSL, and the performance of the TECSL can be improved by appropriately changing the lens focal length.